2022
DOI: 10.1101/2022.08.26.505374
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Effect of reduced genomic representation on using runs of homozygosity for inbreeding characterization

Abstract: Runs of homozygosity (ROHs) are proxy for genomic Identical-by-Descent segments and are increasingly used to measure individual inbreeding. ROHs analyses are mostly carried out on SNPs-arrays and whole-genome-sequencing data. Softwares recurrently used for their detection usually assume that genomic positions which have not been genotyped are non-variant. This might be true for whole-genome-sequencing data, but not for reduced genomic representations and can lead to spurious ROHs detection. We simulated the ou… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 86 publications
0
4
0
Order By: Relevance
“…We used RZooRoH (Bertrand et al, 2019) to detect ROH in our sampled individuals although we acknowledge that the use of reduced representation and lcWGS for ROH detection is still a fraught process (Duntsch et al, 2021;Lavanchy and Goudet, 2022). Despite diZerences in absolute estimates of FROH there is strong correlation between methods and data types (Duntsch et al, 2021) suggesting that relative comparisons are eZective even with sparse data.…”
Section: High Inbreeding In the Wild And In Captivitymentioning
confidence: 99%
See 2 more Smart Citations
“…We used RZooRoH (Bertrand et al, 2019) to detect ROH in our sampled individuals although we acknowledge that the use of reduced representation and lcWGS for ROH detection is still a fraught process (Duntsch et al, 2021;Lavanchy and Goudet, 2022). Despite diZerences in absolute estimates of FROH there is strong correlation between methods and data types (Duntsch et al, 2021) suggesting that relative comparisons are eZective even with sparse data.…”
Section: High Inbreeding In the Wild And In Captivitymentioning
confidence: 99%
“…Across samples, we expect there to be little bias introduced by diZerences in mean depth of coverage, as the wild individuals have the lowest mean depth (Supplementary Table 1) but the greatest number of short ROH (Figure 2bc). With incomplete representation of the genome, ROH detection methods tend to underestimate the number of short ROH (Lavanchy and Goudet, 2022), therefore the dropout of sites due to low depth in the wild individuals has not substantially biased the estimation of relative FROH and ROH tract lengths. The estimation of FROH with such approaches is less sensitive to data quality than is the determination of the precise coordinates of ROH (Duntsch et al, 2021;Lavanchy and Goudet, 2022).…”
Section: High Inbreeding In the Wild And In Captivitymentioning
confidence: 99%
See 1 more Smart Citation
“…One advantage of these methods is that they do not depend on allelic frequencies which can be very valuable when only a few individuals are available. However, it has been shown that these coefficients, and especially F ROH , are sensitive to SNP density and parameters used, and there is no consensus on what is the most suitable set of parameters at present [23,18]. How to quantify ID, although central to conservation genetics for decades [16], is still debated.…”
Section: Introductionmentioning
confidence: 99%